Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1016/j.tate.2012.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Institutional conceptualisations of teacher education as academic work in England

Abstract: Abstract:Through an analysis of job recruitment texts, and interviews with academic leaders, this article shows how the university-based teacher educator is produced as a category of academic worker in England. Focusing on the discursive processes of categorisation provides insights into how English universities conceptualise teacher education. Variations in conceptualisations are noted within and between institutions, with the teacher educator produced as a hybrid or exceptional category. Often, variations ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 13 publications
2
32
0
Order By: Relevance
“…Accompanying this is an emerging scholarship around the kinds of work that university based TEs do (Murray, 2008;Ellis, McNicholl & Pendry, 2012;Nuttall et al 2013). …”
Section: Accepted For Publication Version -Pre--proof and Correctionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Accompanying this is an emerging scholarship around the kinds of work that university based TEs do (Murray, 2008;Ellis, McNicholl & Pendry, 2012;Nuttall et al 2013). …”
Section: Accepted For Publication Version -Pre--proof and Correctionsmentioning
confidence: 99%
“…In England, Ellis, McNicholl and Pendry (2012) describe how it is possible to interpret TE as a troublesome category of academic worker by virtue of universities' contradictory expectations of TEs and their work. Reinforcing this sentiment is a sense that TEs may be considered reluctant researchers (Saito, 2013), or that they work under conditions where research is difficult to conduct (Brennan & Willis, 2009) or in situations where their capacity for research is still to be built (Hill & 1 Recent changes (1 July 2015) in NZ have added a requirement for teachers to possess an ongoing certification to teach.…”
Section: Accepted For Publication Version -Pre--proof and Correctionsmentioning
confidence: 99%
“…International research similar to our own was identified through systematic search procedures as described by Depaepe, Verschaffel and Kelchtermans (2013). Work by Adamson (2012), Delandshere andPetrosky (2004), Ellis, McNicholl and Pendry (2012), Sleeter (2008), Zeichner (2010) was identified. It suggested similar ideas, that certain common policy presuppositions can be identified regarding teacher education programmes in advanced knowledge-based economies and at the level of institutions (Hökkä, Eteläpelto, & Rasku-Puttonen, 2010) and that a recent ideological and rather unscientific policy process had emerged challenging these intentions (Reid & O'Donoghue, 2004) and the development of critically conscious and creative teaching professionals (Garm & Karlsen, 2004;Zeichner, 2010).…”
Section: The Research Focusmentioning
confidence: 99%
“…This might not be uncommon also internationally if we read with for instance Adamson (2012), Apple (2001), Delandshere and Petrosky (2004), Reid and O'Donoghue (2004) and Zeichner (2010). In addition, teacher educators seem to have been unable to develop effective strategies for communicating the importance of a broader conception of professional knowledge needs for teaching in teacher education (Ellis, McNicholl & Pendry, 2012;Hökkä, Eteläpelto, & Rasku-Puttonen, 2010).…”
Section: Teacher Education Policies Seem To Be Based On Ideologicallymentioning
confidence: 99%
See 1 more Smart Citation